THE EFFECT OF DIFFERENT LIGHT CURED UNIT INTENSITIES ON THE DEPTH OF POLYMERIZATION OF BULK FILL SCULPTABLE COMPOSITE RESIN RESTORATIONS - Alphania Esty Luthfaida; Arlina Nurhapsari; Helmi Fathurrahman (Jurnal Medali, 2021)
Background : The latest development of dental material restoration is a bulk fill sculptable composite resin. This material can be applied to a 4 mm cavity at once irradiation. The success of polymerization can be affected by improper irradiation. Both the physical and mechanical properties of the material also can be decreased by improper irradiation. This study aimed to determine the effect of different light-cured unit intensities on the depth of polymerization of bulk fills sculptable composite resin restorations.Method : This research method was an experimental analytic type of post-test only control group design laboratory, consisting of 24 bulk fill sculptable composite resin with a diameter of 4mm x 6mm thickness divided into 6 groups:A1(3M ESPE-low intensity),A2(3M ESPE-high intensity),A3(3M ESPE-soft start intensity),B1(Ivoclar vivacity-low intensity),B2(Ivoclar vivadent-high intensity) and B3(Ivoclar vivadent-soft start intensity). Result : The results showed a significant effect of the low, high, and soft start intensity light-cured units in the bulk fill sculptable composite resin groups by Kruskal-Wallis test 0.00 (p <0.05).Conclusion : The best polymerization depth of bulk fill sculptable composite resin was 3M ESPE and it was affected by the high and low-intensity light-cured units